PENGEMBANGAN MASYARAKAT BERBASIS KEARIFAN LOKAL - Zainal Zainal (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
Although humans including an important part in the development of communities in improving the interaction among humans , but the human factor is difficult to remove subjectivity in color and direct the development of a model of society . Real human interaction with the local conditions surrounding pretty determine the balance of society . Therefore, it should be noted human sensitivity and concern for the local strength in which he lived and interacted . In this context , it is reasonable local wisdom used as a model in the development of society . Related to that , the handling of social problems that occur today , can be addressed effectively if the community has been powerless in understanding local wisdom